Homogeneously sized groups increase aggressive interaction and affect social stress in Thai strain Nile tilapia (Oreochromis niloticus) - Barreto, Tatiana Nunes [UNESP]; Boscolo, Camila Nomura Pereira [UNESP]; Gonçalves-de-Freitas, Eliane [UNESP] (Taylor & Francis, 2015)
Social fish raised in farms are usually kept in groups of similar-sized individuals. However, social animals of similar size typically have similar fighting ability, which increases aggressive interaction for social rank establishment, as well as social stress. We compared Thai strain Nile tilapia fish, Oreochromis niloticus (L.), held under two treatments: (1) The Homogeneous one, with five adult male fish of similar size and (2) the Heterogeneous treatment with five adult males of different sizes. We recorded the frequency of aggressive interactions and checked social stability and stress levels (cortisol) after five days in the groups. Grouping similar sized Thai Nile tilapia increased the aggressive interactions and delayed rank stability with increased body injuries as a consequence. Homogeneous-sized individuals showed a similar level of stress while heterogeneous-sized individuals showed different stress levels with dominants being more stressed than subordinates. The data indicate that the practice of selecting fish of similar size in aquaculture management could reduce the welfare of social fish and that the effect is observed in different lineages.
Keywords: aggression; culture; Nile tilapia Oreochromis niloticus; size selection; stress; welfare